2013
DOI: 10.1177/0164027512475096
|View full text |Cite
|
Sign up to set email alerts
|

Companionship in the Neighborhood Context

Abstract: This study investigated the impact of neighborhood social cohesion on the perceived companionship of nearly 1,500 community-dwelling older adults from the Neighborhood, Organization, Aging and Health project (NOAH), a Chicago-based study of older adult well-being in the neighborhood context. We hypothesized that the relationship between neighborhood-level social cohesion and individual residents’ reports of companionship would be more pronounced among those who lived alone than those who resided with others. C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
24
0
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 63 publications
(28 citation statements)
references
References 41 publications
2
24
0
2
Order By: Relevance
“…Another study, this one of older Hispanic immigrants in Miami, Florida, found that individuals’ more positive perception of their neighborhood social environment was directly associated with better cognitive functioning and indirectly associated with lower depressive symptoms and anxiety through perceived satisfaction with instrumental social support and positive social interactions (Brown et al, 2009). A study of older Chicagoans also found that higher perceived neighborhood social cohesion was associated with more companionship among those who lived alone, though not among those who resided with others, suggesting that solo-living older adults are more likely to benefit from a supportive social environment (Bromell & Cagney, 2014). …”
Section: Introductionmentioning
confidence: 99%
“…Another study, this one of older Hispanic immigrants in Miami, Florida, found that individuals’ more positive perception of their neighborhood social environment was directly associated with better cognitive functioning and indirectly associated with lower depressive symptoms and anxiety through perceived satisfaction with instrumental social support and positive social interactions (Brown et al, 2009). A study of older Chicagoans also found that higher perceived neighborhood social cohesion was associated with more companionship among those who lived alone, though not among those who resided with others, suggesting that solo-living older adults are more likely to benefit from a supportive social environment (Bromell & Cagney, 2014). …”
Section: Introductionmentioning
confidence: 99%
“…Research shows that ICTs have enabled older adults to remain engaged with diverse network members (Bromell and Cagney 2014;Cotten et al 2013). Turning to ICTs garners a sense of being there and being connected even if in-person contact is not frequent.…”
Section: Facilitating Interpersonal Contactmentioning
confidence: 99%
“…Neighbourhood cohesion may be a key element in youths' community engagement. Neighbourhoods that are more socially cohesive can cultivate social exchanges and companionship, which can consequently promote community participation (e.g., Bromell & Cagney, 2014;Forrest & Kearns, 2001). Conversely, weaker cohesion can reduce social interactions (Forrest & Kearns, 2001) and decrease community participation (e.g., Latham & Clarke, 2016).…”
Section: Pathways To Youth Volunteerism: the Importance Of Neighbourhmentioning
confidence: 99%